Updates to the Stonefly Fauna of Illinois and Indiana - DeWalt, R. Edward (Illiesia, 2011)
In a first phase for reconstructing the stonefly fauna of the Midwest (Ohio, Indiana, Illinois, southern Ontario, Michigan, and Wisconsin) we present updates for the Illinois and Indiana stonefly fauna. Data presented here represent over 11,000 records from the Illinois Natural History Survey and several regional museums. We present three additions to the Illinois fauna, 13to the Indiana fauna, remove Amphinemura nigrita (Provancher) from both state lists, and provide records for many other species. Illinois supports or supported at least 79 species, while the number for Indiana is 87. The two states share 70 species or 84% of the fauna between them. While Illinois has lost 20 species (25.3%), Indiana has lost 10 (11.5%), mostly from the Wabash and White River drainages. Till plain areas in northern Indiana have fared better than those in Illinois because surficial deposits are sand that promotehigh groundwater recharge. Areas of high diversity remaining in the two states are concentrated in the unglaciated southern landscapes.
Keywords: entomology; stoneflies; Illinois; Plecoptera; Indiana; extirpation; conservation; entomologija; vrbnice